2015
DOI: 10.15406/jamb.2015.02.00023
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus mycoides Improves Health of Gastrointestinal Tract in Marron (Cherax cainii, Austin 2002)

Abstract: The present study examined the health status of the gastrointestinal tract (GIT) in marron after a two-month feeding trial with a diet supplemented with host origin, Bacillus mycoides. Two groups of marron were fed with either a basal diet or probiotic added at 10 8 cfu/g of feed. Microbial density, microvilli length and number, intestinal epidermis layer morphology and hepatopancreas indices of weight and moisture content were evaluated. Supplementation with B. mycoides in marron feed significantly improved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Before use, the pelleted diet was homogenised with a blender to obtain a desirable pellet size before supplementation with the B. mycoides at 10 8 cfu/g of feed. The density of B. mycoides was based on the density used in other Bacillus species studies [32][33][34][35][36] and from results of our previous studies [18,19]. Supplementation of the probiotic followed established methods [37].…”
Section: Experimental Diet and Set Upmentioning
confidence: 99%
See 1 more Smart Citation
“…Before use, the pelleted diet was homogenised with a blender to obtain a desirable pellet size before supplementation with the B. mycoides at 10 8 cfu/g of feed. The density of B. mycoides was based on the density used in other Bacillus species studies [32][33][34][35][36] and from results of our previous studies [18,19]. Supplementation of the probiotic followed established methods [37].…”
Section: Experimental Diet and Set Upmentioning
confidence: 99%
“…Our previous studies indicated that Bacillus mycoides, a marron origin customised probiotic, possessed a number of favourable probiotic properties [17], significantly improved gastrointestinal (GIT) health of marron [18] and improved immunity against the pathogenic bacterium Vibrio mimicus [19], a dominant bacterial pathogen of freshwater crayfish in aquaculture [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, B. mycoides was selected as it was of host origin and possessed a number of probiotic properties (Ambas, Buller et al . ) such as improved marron immunity against V. mimicus (Ambas et al . ) and improved GIT health status (Ambas, Fotedar et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sel‐plex, an organic form of selenium derived from yeast produced by Alltech, showed beneficial effects in marron when administered at 0.2 g kg − 1 of feed (Nugroho & Fotedar ). Bacillus mycoides, a strain isolated from the gastrointestinal tract of marron, demonstrated favourable probiotic properties such as growth inhibition of Vibrio mimicus and Vibrio cholerae non‐01 (Ambas, Buller & Fotedar ), and improvement in marron health and immunity (Ambas, Suriawan & Fotedar ; Ambas, Fotedar & Buller ). The present study examined the synbiotic effect of the probiotic B. mycoides and the prebiotic OS (Sel‐Plex) on growth, health condition and immunity as tested by total haemocyte count (THC), DHC, bacteraemia, clotting time and glutathione peroxidase ( GP x) enzyme activity of marron.…”
Section: Introductionmentioning
confidence: 99%
“…7,19 Bacillusmycoidesis a predominated bacterium isolated from a number of healthy adult farmed marron GIT that exhibit favourable probiotic properties such as non-pathogenicity to marron, antagonism ability towards common crayfish pathogens (Vibrio mimicus and V. cholerae non-01), exhibition of a diverse enzyme profiles and nonsusceptible to the majority of antibiotics tested 20 improved immunity 21 and the gastrointestinal health status of marron. 22 To date, evaluating probiotic performance in vivo studies is limited to tiger shrimp Penaeusmonodon, 23 shrimp Litopenaeusvannamei 24 and beluga Husohuso. 25 When evaluating probioticsin vivo for its nutritional benefit outcomes in aquatic animals, the probiotic candidates should be added to the diet and its effect evaluated on the growth and/or physiological status of the animals.…”
Section: Introductionmentioning
confidence: 99%